Carbon capture by absorption – Path covered and ahead. (September 2017) - Sreedhar, I.; Nahar, Tanisha; Venugopal, A.; Srinivas, B.
Abstract: Global warming and associated climate change has resulted in serious efforts towards reducing greenhouse gas emissions, primarily carbon dioxide through carbon capture. There are various technical options in pre- and post-combustion modes available viz., adsorption, absorption, membrane separation, chemical looping combustion with and without oxygen uncoupling and cryogenic separations. Among all these, absorption technology which could be deployed as a post-combustion option to be integrated with power plant, has been commercialized with amines as solvents long back. But there is a long way to go to improve this process in terms of economic viability due to large regeneration costs involved and to make it more environmental friendly with minimum toxic and corrosion problems due to solvents. In this review, absorption based carbon capture has been reviewed comprehensively and critically in terms of various aspects like solvents and their synthesis protocols, performance analysis of different solvent systems, contactors, kinetics and thermodynamics, modeling and simulation studies etc. Every section has been discussed in terms of the trends and developments observed including the contemporary status besides citing future challenges and prospects to improve the technology.